Composite power system reliability - Bermudez, Aimee Carla G. (2004)
This project used a state enumeration technique and a probabilistic method of evaluating a composite generation and transmission power system's reliability to be able to classify the system's state. A composite system was classified as being in a healthy, alert, or emergency state. Using the IEEE Reliability Test System as test system, the effect of generating unit outages and transmission line failures on the reliability of the system were evaluated. A combination of five transmission lines and three generating units were considered. Critical generators, transmission lines and buses were determined. This project aimed to quantify the health of the composite power system, and also to provide an approach in identifying significant points and components of the power system.